A tale of two utopias the political journey of the generation of 1968 - Berman, Paul 1949- (Norton, 1996)
A Tale of Two Utopias is the story of the generation of 1968 - not the whole story, (which could never squeeze into a single book), but four representative episodes. It is the story of student radicalism in the years around 1968 - in America and around the world. The story of gay liberation and of modern identity politics - from their origins in the American New Left to the present. The story of the '68ers in the Eastern bloc - and how in 1989, in Czechoslovakia, the '68ers overthrew Communism. And it is the story of the thinkers in America and in France who have lived through these events, the leftism of 1968 and the liberal revolutions that broke out in 1989 - and have debated their meaning. Andre Glucksmann and the New Philosophers of Paris, Tom Hayden and Students for a Democratic Society, the Gay Liberation Front, Frank Zappa, Vaclav Havel and the Velvet Revolution, Francis Fukuyama and his "End of History" - those are the faces and figures of A Tale of Two Utopias.